Safety and effectiveness of dipeptidyl peptidase-4 inhibitors versus intermediate-acting insulin or placebo for patients with type 2 diabetes failing two oral antihyperglycaemic agents: a systematic review and network meta-analysis. Issue 12 (23rd December 2014) - Tricco, Andrea C; Antony, Jesmin; Khan, Paul A; Ghassemi, Marco; Hamid, Jemila S; Ashoor, Huda; Blondal, Erik; Soobiah, Charlene; Yu, Catherine H; Hutton, Brian; Hemmelgarn, Brenda R; Moher, David; et al.
Abstract : Objective: To evaluate the effectiveness and safety of dipeptidyl peptidase-4 (DPP-4) inhibitors versus intermediate-acting insulin for adults with type 2 diabetes mellitus (T2DM) and poor glycaemic control despite treatment with two oral agents. Setting: Studies were multicentre and multinational. Participants: Ten studies including 2967 patients with T2DM. Interventions: Studies that examined DPP-4 inhibitors compared with each other, intermediate-acting insulin, no treatment or placebo in patients with T2DM. Primary and secondary outcome measures: Primary outcome was glycosylated haemoglobin (HbA1c). Secondary outcomes were healthcare utilisation, body weight, fractures, quality of life, microvascular complications, macrovascular complications, all-cause mortality, harms, cost and cost-effectiveness. Results: 10 randomised clinical trials with 2967 patients were included after screening 5831 titles and abstracts, and 180 full-text articles. DPP-4 inhibitors significantly reduced HbA1c versus placebo in network meta-analysis (NMA; mean difference (MD) −0.62%, 95% CI −0.93% to −0.33%) and meta-analysis (MD −0.61%, 95% CI −0.81% to −0.41%), respectively. Significant differences in HbA1c were not observed for neutral protamine Hagedorn (NPH) insulin versus placebo and DPP-4 inhibitors versus NPH insulin in NMA. In meta-analysis, no significant differences were observed between DPP-4 inhibitors and placebo for severe hypoglycaemia, weight gain, cardiovascular disease, overall harms, treatment-related harms and mortality, although patients receiving DPP-4 inhibitors experienced less infections (relative risk 0.72, 95% CI 0.57 to 0.91). Conclusions: DPP-4 inhibitors were superior to placebo in reducing HbA1c levels in adults with T2DM taking at least two oral agents. Compared with placebo, no safety signals were detected with DPP-4 inhibitors and there was a reduced risk of infection. There was no significant difference in HbA1c observed between NPH and placebo or NPH and DPP-4 inhibitors. Trial registration number: PROSPERO # CRD42013003624.